ANALISIS TINGKAT KEPUASAN PASIEN BPJS DAN NON BPJS TERHADAP MUTU PELAYANAN DI RUANG RAWAT INAP RSUD GUNUNG TUA.: ANALISIS TINGKAT KEPUASAN PASIEN BPJS DAN NON BPJS TERHADAP MUTU PELAYANAN DI RUANG RAWAT INAP RSUD GUNUNG TUA - Pohan, Tiasa (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
abstrac Patient satisfaction is a key aspect of both inpatient and outpatient services, and it has been shown that there is a strong relationship between the treatment of health workers and patient satisfaction through previous research. Complaints from patients or their families are one quality indicator related to patient satisfaction. By knowing the level of patient satisfaction, hospital management can improve the quality of service. This research method is quantitative with a comparative design. This research was carried out in the Inpatient Room of North Padang Lawas Regional Hospital with a sample of 88 people consisting of 44 BPJS samples and 44 non-BPJS samples taken using the quota sampling technique. The results of the research show that the majority of BPJS stated that service quality was good in the dimensions of tangible, reliability, responsiveness, assurances, empathy and feeling satisfied, namely 18 people (40.9%), 20 people (45.5%), 17 people respectively. (38.6%), 19 people (43.2%) and 18 people (40.9%). The majority of non-BPJS stated that service quality was good in the dimensions of tangible, reliability, responsiveness, assurances, empathy and satisfied respectively. respectively 19 people (43.2%), reliability dimension 21 people (47.7%), responsiveness dimension 20 people (45.5%), assurance dimension 20 people (45.5%) and empathy dimension 18 people (40 .9%). There is a difference in the level of satisfaction of BPJS and non-BPJS patients with service quality with the p value of tangible dimension service quality = 0.001, reliability = 0.001, responsiveness = 0.001, assurances = 0.000 and empathy = 0.001 which indicates the p value is smaller than the α value = 0.05 Suggestions to the Gunung Tua Regional Hospital to always improve services to inpatients without distinguishing between BPJS and non-BPJS status.